A comparative study of laws and policies impacting the conservation of biodiversity with special reference to agricultural biodiversity - Laxman, Lekha Kunju Pillai (Ahmad ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2015)
The process of rapid development comes with a price and it is mostly done at the expense of biodiversity and general environmental degradation. The complex interrelationship between agricultural biodiversity and biotechnology as well as the conflicting institutional interplay in the international governance of the conservation and use of plant genetic resources has resulted in a trade-environment deadlock between the technologically advanced developed nations and genetically resource rich developing and least developed nations to the detriment of the collective interests of the global community. The aim of the current research is to investigate the origins, operations and effects of legal regimes, policies and practices related to conservation of biodiversity. It undertakes a comparative study of laws and policies in this area to gain an in-depth understanding of the factors behind the lack of success in conserving biodiversity in general and agricultural biodiversity in particular and explores ways in which the conflicts between the WTO Agreements and the CBD can be resolved. The research undertook a socio-legal approach utilizing a qualitative research method which predominantly relied on content analysis of provisions in the various treaties that had a bearing on conservation of biodiversity as well as decided cases, reports and studies that analyzed the implementation of these treaties. The findings of the study indicated that global governance structures such as the WTO and the CBD have to reinvent themselves in order to meet the challenges of the millennia brought about by cutting edge technologies such as modern biotechnology. The global community also must have an Ubuntu mindset i.e. unity consciousness to tackle global challenges such as biodiversity loss and global warming which threatens the wellbeing of the planet and its inhabitants. Without such a mindset, no technology, policies or laws will be able to avert the global crises which may culminate into massive extinctions and jeopardize the future of this planet. We need to ensure that our policies and laws are entrenched with ethical values promoted at the global level aimed at ensuring the wellbeing of all.